2018
DOI: 10.1017/s0142716418000383
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary size and native speaker self-identification influence flexibility in linguistic prediction among adult bilinguals

Abstract: When language users predict upcoming speech, they generate pluralistic expectations, weighted by likelihood (Kuperberg & Jaeger, 2016). Many variables influence the prediction of highly likely sentential outcomes, but less is known regarding variables affecting the prediction of less-likely outcomes. Here we explore how English vocabulary size and self-identification as a native speaker (NS) of English modulate adult bi-/multilinguals’ preactivation of less-likely sentential outcomes in two visual-world ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Lexical knowledge has been suggested to underlie prediction abilities (e.g., Peters et al, 2018). One hypothesis, the "prediction by production" hypothesis, presented by Pickering and Gambi (2018),…”
Section: Prediction and Bilingualismmentioning
confidence: 99%
“…Lexical knowledge has been suggested to underlie prediction abilities (e.g., Peters et al, 2018). One hypothesis, the "prediction by production" hypothesis, presented by Pickering and Gambi (2018),…”
Section: Prediction and Bilingualismmentioning
confidence: 99%
“…Recently, there has been an increase in studies exploring L2 predictive processing (Godfroid, 2020). Research has provided ample evidence that L2 listeners can make predictions based on lexical-semantic cues (e.g., Dijkgraaf et al, 2017Dijkgraaf et al, , 2019Peters et al, 2018). In contrast to L1 prediction, the outcomes regarding L2 prediction based on morphosyntactic cues have been more mixed.…”
Section: L1 and L2 Predictive Sentence Processingmentioning
confidence: 99%
“…To wrap up, one possible explanation for the variability in study outcomes is a difference in complexity: if complexity increases, be it linguistically or non-linguistically, differences in prediction between L1 and L2 processing are more likely to occur. Complexity, and with that uncertainty on the part of the L2 speakers, may increase even more when the visual display not only contains multiple images, but when it contains competitor imagesas, for instance, shown by Peters, Grüter andBorovsky (2018) (but cf. Ito, Corley &, who found that a semantic competitor image did not receive more fixations than two distractor images).…”
Section: Complexitymentioning
confidence: 99%
“…Ito, Corley &, who found that a semantic competitor image did not receive more fixations than two distractor images). Peters et al (2018) presented a large heterogeneous group of bilingual speakers with sentences such as The pirate chases the ship while the visual display, in addition to the target image (ship), contained the image of an agent-related object (treasure), an action-related object (cat), and an unrelated object (bone). The authors found that the consideration of competitor images was more pronounced in bilingual speakers who had a smaller vocabulary and/or speakers who indicated themselves as non-native speakers of English: lowvocabulary bilingual speakers and self-indicated L2 speakers were more likely to consider the image of a cat upon listening to the action verb than high-vocabulary speakers and speakers who considered themselves as native speakers.…”
Section: Complexitymentioning
confidence: 99%